1984
DOI: 10.2527/jas1984.581244x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Degradation in the Rumen and Amino Acid Absorption in the Small Intestine of Lactating Dairy Cattle Fed Various Protein Sources

Abstract: Four lactating Holstein cows fitted with a rumen cannula and T-type cannulae in the duodenum and ileum were used in an experiment with a 4 X 4 Latin square arrangement of treatments. Diets containing soybean meal (SBM), corn gluten meal (CGM), wet brewers grains (WBG) and distillers dried grains with solubles (DDG) were compared with regard to protein degradability in the rumen and amino acid flow and absorption in the small intestine. The test protein sources provided about 50% of the dietary protein. Spot sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
38
1
7

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 24 publications
13
38
1
7
Order By: Relevance
“…Santos and Pedroso (2011) emphasized that the reduction in microbial production may be related to lower carbohydrate availability and lower dietary protein degradability for protein synthesis. This can explain the results of the current study because, according to Santos et al (1984), brewers' grains generate a smaller contribution of ammonia N due to lower ruminal degradable CP present in this feed. Additionally, diets with higher DBG levels also had lower corn proportions (Table 1), which reduced the availability of rapidly fermenting carbohydrates, limiting microbial growth and protein synthesis.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Santos and Pedroso (2011) emphasized that the reduction in microbial production may be related to lower carbohydrate availability and lower dietary protein degradability for protein synthesis. This can explain the results of the current study because, according to Santos et al (1984), brewers' grains generate a smaller contribution of ammonia N due to lower ruminal degradable CP present in this feed. Additionally, diets with higher DBG levels also had lower corn proportions (Table 1), which reduced the availability of rapidly fermenting carbohydrates, limiting microbial growth and protein synthesis.…”
Section: Discussionsupporting
confidence: 72%
“…The CP digestibility was high because, although the brewers' grains present low ruminal degradability, high intestinal digestibility (Santos et al, 1984) leads to a high total apparent digestibility. This was also reported by Geron et al (2007), who found larger amounts of rumen undegradable protein but degradable in the small intestine with fermented beer residue (394 g kg -1 CP) compared with soybean meal (187 g kg -1 CP).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, groups of comparisons were tested for homogeneity between and within groups. All data were taken or calculated from experiments reported in 57 independent studies (Kung et al, 1983;Stern et al, 1983;Prange et al, 1984;Robinson and Sniffen, 1984;Santos et al, 1984;Robinson et al, 1985;Rode et al, 1985;Stern et al, 1985;Armentano et al, 1986;Lu et al, 1988;Price et al, 1988;McCarthy et al, 1989;Waltz et al, 1989;Herrera-Saldana et al, 1990;King et al, 1990;Klusmeyer et al, 1990Klusmeyer et al, , 1991aCameron et al, 1991;Lynch et al, 1991;Ohajuruka et al, 1991;Stokes et al, 1991;Erasmus et al, 1992Erasmus et al, , 1994Aldrich et al, 1993;Christensen et al, 1993aChristensen et al, , 1996Cunningham et al, 1993Cunningham et al, , 1994Cunningham et al, , 1996Feng et al, 1993;Poore et al, 1993;Tice et al, 1993;Benchaar et al, 1994;Pantoja et al, 1994Pantoja et al, , 1995Calsamiglia et al, 1995;Oliveira et al, 1995;Overton et al, 1995;Yoon and Stern, 1996;Chan et al, 1997;…”
Section: Statistical Analysis Of Data From Literaturementioning
confidence: 99%
“…This demonstrates the excessive intake of protein in the diet and an energy deficit or lack of synchronisation of degradable and non-degradable fractions in the rumen (SANTOS et al, 1984). This is because there is a direct relationship between blood concentrations of urea nitrogen with dietary protein intake, as well as the energy: protein ratio (CLAYPOOL et al, 1980;CONTRERAS, 2000).…”
Section: Resultsmentioning
confidence: 99%